Tocando - Dorling Kindersley (Buenos Aires : Sigmar., 1992)
Labeled pictures depict things one can touch that are wet, rough, soft, smooth, furry, prickly, squishy, and sticky.
Translation of: My first look at-- touch.
"Un libro Dorling Kindersley"--T.p. verso.
Keywords: Touch -- Juvenile literature; Senses and sensation -- Juvenile literature